SOCIOLOGICAL OBSERVATION OF AFRICAN CULTURAL VALUES IN THE LIGHT OF MODERNITY: THE EXPERIENCE OF YORUBA IN NIGERIA - Rotimi, Odudele (PEOPLE: International Journal of Social Sciences, 2016)
Traditional Africans are grossly endowed with rich and unprecedented cultural values with which harmony, solidarity, orderliness, sanctity and sanity are ensured within their community. Despite the fact that there were no trained and armed security officers in the olden days as we have today, yet their communities were void of chaos. In view of this, this paper is set to examine some of these African cultural values and how the force of modernity has influenced its observance with a particular reference to the Yoruba of Nigeria. An attempt also will be made to discuss the concept of modernity and equally on how African cultural values were enforced in the traditional societies. In conclusion, recommendations will be made on the need to revive the African cultural values as a panacea to the high level of moral decadence in the modern African societies.